2022
DOI: 10.1177/11207000221093248
|View full text |Cite
|
Sign up to set email alerts
|

A 24-year single-centre experience with Collum Femoris Preserving stem: clinical and radiological results in young and elderly population

Abstract: Objective: The primary aim was to evaluate the long-term follow-up of Collum Femoris Preserving (CFP) stem, specifically focusing on stem survivorship, complications, as well as on clinical and radiological results. The secondary study objective is an age-based sub-analysis (<65 years vs. ⩾65 years) of long-term results. Materials and methods: We performed a retrospective analysis of patients who underwent CFP implantation between 1997 and 2009. A total of 311 patients (342 hips) were included with a mean f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The influence of chance is high because of the limited sample size. Earlier studies reported revision rates between 10% and 27% for the CFP stem [ 11 , 13 ] and 2% and 8% for the Zweymüller stem [ 27 - 30 ]. However, 2 of the revisions in our study were solitary cup revisions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The influence of chance is high because of the limited sample size. Earlier studies reported revision rates between 10% and 27% for the CFP stem [ 11 , 13 ] and 2% and 8% for the Zweymüller stem [ 27 - 30 ]. However, 2 of the revisions in our study were solitary cup revisions.…”
Section: Discussionmentioning
confidence: 99%
“…No strong conclusions can be drawn on implant survival because this trial was not statistically powered for survival analysis. When looking at observational studies, we also see higher revision rates for the CFP than for the Zweymüller stem [ 11 - 13 , 27 - 30 ]. Although not statistically significant, our RCT supports these findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation